PARTAI POLITIK & POLITIK HIJAU: Studi tentang Kepedulian Parpol terhadap Politik yang Prolingkungan di Kota Semarang - SUPRATIWI, SUPRATIWI (Politika: Jurnal Ilmu Politik, 2011)
AbstractThe purpose of the research is to seek political parties awareness on green politics inSemarang City. It is conducted towards the big five political parties according to 2009 election: PartaiDemokrat (Democrat Party), Partai Demokrasi Indonesia Perjuangan/PDI-P (Indonesian StruggleDemocratic Party), Partai Amanat Nasional/PAN (National Mandate Party), Partai KeadilanSejahtera/PKS (Justice and Prosperity Party), and Partai Golongan Karya (Functional Group Party)as they have power to make decision in Semarang City legislature including environmental policy.Using descriptive qualitative method, the research was conducted by interviewing the legislators,observation, and also documents analysis. The result is clear that political parties do not haveawareness on green politics as well as environmental issues. It is reflected on the lack ofenvironmental awareness within their vision, mission, platform, and programs. Ironically, during theprevious legislature, political parties had many things to do to solve environmental problems, such asflood. They initiated many policies to build pond, increasing city’s environmental budget, and alsoenacting law of landscape. However, for the recent legislature it has not been planned yet.Keyword: awareness, political parties, green politics